INSTRUMEN ATURAN-ATURAN BANGUNAN DALAM PENGENDALIAN PEMBANGUNAN DI KOTA SURAKARTA - Dinilla Husna; Imam Buchori (Diponegoro University, 2008)
Building permit (Ijin Mendirikan Bangunan/IMB) is one of the development control mechanism inIndonesia that allows people to develop their land. The idea in using this permit to control developmentmay come from a reasonable thought, i.e. managing building as the core of urban development will be ableto create a proper urban planning. Therefore, as one of control system, building permit has to followregulations that have been determined by the authority.Concerning the issue above, Surakarta’s municipality has determined a bundle of regulation functioned asguidance for permit decision into a municipal regulation (Peraturan Daerah/ Perda) as well as conventionregulation. That regulation control Building Coverage Ratio (Koefisien Dasar Bangunan/KDB), FloorAverage Ratio (Koefisien Lantai Bangunan/KLB), Set Back Building (Garis Sempadan Bangunan), andBuilding Height. Unfortunately, the implementation of that regulation is frequently questioned because theprocedure and the phenomenon of building permit which has been issued by the local government was noteffectively implemented. Hence, this study aims to answer the question on to what extent the buildingregulation has been used in controlong urban land development in Surakarta.This study uses comparative and qualitative descriptive analyses. The first analysis aims to observewhether that regulation have been considered in issuing a building permit. The second analysis is used toidentify how the factors above influence the implementation of that regulation. The triangulation techniquethat combines desk study, interview with the apparatus, questioners for IMB owners, and direct observationwas used to collect the data.The result of study shows that building permit was not issued based on the available regulation andmoreover not considered as a preventive action to control land development. The deviation between thedetermined ragulation and the building permit issued was affected by some factors, e.g. bureaucracysystem that does not use them as a control function to integrate permit decisions, low commitment of localgovernment staffs in controlling land development, and political intervention from its higher level of localgovernment authority. To overcome these problems, a brief regulation and a punishment mechanism arecertainly needed. Besides, improvement of apparatus quality, optimization of coordination and watchingsystem in building permit process are supposed to be able to support urban land development.